Concentrations of some minerals in cows with retained placenta and abortion - Akar, Y; Yildiz, H (Tubitak Scientific & Technological Research Council Turkey, 2005)
This study was undertaken to investigate the relationship between blood levels of Ca, Zn, Mg, K, and Na and the occurrence of retained placenta and abortion in cows. Serum samples from 34 cows were analyzed (18 with retained placenta, 10 without retained placenta (control), and 6 that had aborted). Ca and Zn levels in cows with retained placenta were significantly lower than those in the control group. The serum Zn levels of aborted cows were higher (P < 0.001) than those of cows with retained placenta. Cows in the control group and those with retained placenta were divided-into subgroups based on age (3, 4-6, 7-9 years old), type of parturition (normal, dystocia), and sex of calves (male, female). The serum Ca concentration of 3-year-old cows with retained placenta was significantly higher (P < 0.05) than that of those 7-9 years old. It is concluded that lower serum Ca and Zn levels in cows may induce placenta retention.
Keywords: retained placenta; abortion; mineral substance; cow